Analisis Pasar Modal Di Indonesia Studi Pada Perusahaan Manufaktur - Amar, Anis Tassya Regitha Putri; Atmadja, Melvin; Veronica, Novita (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The Government of Indonesia (GoI) recently enacted Government Regulation Number 72/2016 concerning Shares Subscription and Arrangement of State Capitals in State-Owned Enterprises (BUMN) (hereinafter referred to as “PP Holding BUMN”). The Indonesian Ministry for BUMN (“Meneg BUMN”) proposes, that the Holding of BUMN will cover six core economic sectors: (1) Energy, (2) Mineral extraction, (3) Financial service, (4) Highway infrastructure/construction, (5) Property (real estate), (6) Food. BUMN is principally regulated in Article 33 paragraphs 1, 2, and 3 of the Indonesian Constitution 1945, which provides a legal basis for the state-owned monopolies by BUMN. On one hand, the GoI argues that Holding of BUMN is necessary because it would bring beneficial impacts, such as the strengthening of corporate performance by creating synergies and economies of scale and reducing inefficiencies in operations and financing; professionalizing the management system by distancing BUMN from unreasonable politics; and relieving the Government of its direct responsibilities of overseeing all the BUMN dispersed across various industries. On the other hand, there are public pervasive concerns that PP Holding BUMN would lead to unlawful privatization of BUMN, and this led to the public filing an appeal for a Judicial Review from the Indonesian Constitutional Court. Accordingly, this research attempts to analyze the Holding of BUMN under PP Holding BUMN, the Constitutional Law Analysis of Judicial Review over the Government Regulation Number 47/2017, as well as Law Number 19 year 2003 on BUMN.Keywords: Holding of Indonesian State-Owned Company (BUMN); Government Regulation Number 72/2016; Judicial Review; Indonesian Constitutional Court (MKRI)  AbstrakPemerintah Indonesia baru-baru ini menetapkan Peraturan Pemerintah Nomor 72 Tahun 2016 tentang Langganan Saham dan Penyelenggaraan Modal Negara pada Badan Usaha Milik Negara (BUMN) (selanjutnya disebut "PP Holding BUMN"). Kementerian BUMN mengusulkan bahwa Holding BUMN akan mencakup enam sektor ekonomi inti: (1) Energi, (2) Ekstraksi Mineral, (3) Layanan Keuangan, (4) Infrastruktur/Jalan Raya, (5) Properti (real estat), (6) Pangan. BUMN pada dasarnya diatur dalam Pasal 33 ayat 1, 2, dan 3 Undang-Undang Dasar 1945 Indonesia, yang memberikan dasar hukum bagi monopoli milik negara oleh BUMN. Di satu sisi bahwa Holding BUMN diperlukan karena akan membawa dampak positif, seperti penguatan kinerja perusahaan dengan menciptakan sinergi dan ekonomi skala serta mengurangi ketidakefisienan dalam operasi dan pendanaan; profesionalisasi sistem manajemen dengan menjauhkan BUMN dari politik yang tidak masuk akal; dan meringankan Pemerintah dari tanggung jawab langsung pengawasan terhadap semua BUMN yang tersebar di berbagai industri. Di sisi lain, ada kekhawatiran masyarakat yang meluas bahwa PP Holding BUMN akan mengarah pada privatisasi yang tidak sah dari BUMN, dan hal ini menyebabkan masyarakat mengajukan permohonan Judicial Review ke Mahkamah Konstitusi Indonesia. Oleh karena itu, penelitian ini berusaha untuk menganalisis Holding BUMN sesuai dengan PP Holding BUMN, Analisis Hukum Konstitusional atas Judicial Review terhadap Peraturan Pemerintah Nomor 47 Tahun 2017, serta Undang-Undang Nomor 19 Tahun 2003 tentang BUMN.Kata Kunci : Holding Badan Usaha Milik Negara (BUMN); Peraturan Pemerintah Indonesia No. 72 Tahun 2016; Judicial Review; Mahkamah Konstitusi Republik Indonesia (MKRI)